HUBUNGAN MEROKOK DENGAN KAPASITAS VITAL PARU PADA BURUH PELABUHAN PULAU BAAI BENGKULU TAHUN 2009 - Septiyanti, Septiyanti (Politeknik Kesehatan Kemenkes Bengkulu, 2012)
The ability of the lungs to expand, which mean’s a person’s ability to use respiratory muscles to expand the chest depend on smoking activity and daily activity. The purpose of this research is to know the relationship between smoking with vital lungs capacity of the worker in Baai Island Harbour at 2009. This research using cross sectional design. The independent variable; smoking habits, nutritional status, age and history lungs disease and vital lungs capacity as dependent variable. Sample as 50 people. Data were analyzd by univariat frequency distributions, with bivariate chi-square test. The result of this research there’s a relationship between smoking with vital lungs capacity of the worker in Baai Island Harbour 2009, after controlling disease history (ρ value 0,11, PR 9,20, 95% CI 1,67-50,65. More efforts should be intensified promotion and prevention to stop smoking in public, especially in the productive age group by explaining the effects that can be caused by smoking, both for the smoker himself and for others around them.